Hygrophorus viridiflavidus sp. nov. (Hygrophoraceae, Agaricales), from North China - Zhang, Yu-Xin; Mao, Ning; Fan, Li (Phytotaxa, 2023)
Hygrophorus viridiflavidus, a new species from Shanxi Province in northern China, belonging to subgenus Colorati, section Limacini, is proposed in this study based on morphology and molecular systematics. Hygrophorus viridiflavidus is similar and closely related to H. glutinifer, but can be distinguished from the latter by its shorter and narrower basidia (35.0–46.5 × 8.0–10.5μm). Morphological characteristics and ITS-phylogeny support Hygrophorus viridiflavidus as a distinct species.